Trends in disability prevalence among young people: Insights from the Growing Up in Ireland study - Emer Smyth; Helen Russell (The Economic and Social Research Institute (ESRI), 2024)
This report draws on analyses of the two cohorts of the Growing Up in Ireland (GUI) study to examine trends in the prevalence of disability among 13-year-olds over the decade 2011/2012 to 2021/2022. The report looks at changes over time in the size and composition of those with a long-lasting condition (LLC) or disability, at the presence of socio-emotional difficulties and/or depressive symptoms among these groups, and at a range of adolescent outcomes.
Keywords: 330